Estimation of cost-based prices for injectable medicines in the WHO Essential Medicines List - Dzintars Gotham (BMJ Open, 2019)
Objectives Challenges remain in ensuring universal access to affordable essential medicines. We previously estimated the expected generic prices based on cost of production for medicines in solid oral formulations (ie, capsules or tablets) on the WHO Model List of Essential Medicines (EML). The objectives of this analysis were to estimate cost-based prices for injectable medicines on the EML and to compare these to lowest current prices in England, South Africa, and India.Design Data on the cost of active pharmaceutical ingredients (APIs) exported from India were extracted from an online database of customs declarations (www.infodriveindia.com). A formula was designed to use API price data to estimate a cost-based price, by adding the costs of converting API to a finished pharmaceutical product, including the cost of formulation in vials or ampoules, transportation and an average profit margin.Results For injectable formulations on the WHO EML, medicines had prices above the estimated cost-based price in 77% of comparisons in England (median ratio 2.54), and 62% in South Africa (median ratio 1.48), while 85% of medicines in India had prices below estimated cost-based price (median ratio 0.30). 19% of injectable medicines in England, 9% in South Africa, and 5% in India had prices more than 10 times the estimated cost-based price. Medicines that appeared in the top 20 by ratio of lowest current price to estimated cost-based price for more than one country included numerous oncology medicines—irinotecan, leuprorelin, ifosfamide, daunorubicin, filgrastim and mesna—as well as valproic acid and ciclosporin.Conclusions Estimating manufacturing costs can identify cases in which profit margins for medicines may be set significantly higher than average.